2011
DOI: 10.3758/s13428-011-0157-x
|View full text |Cite
|
Sign up to set email alerts
|

Simple imputation methods versus direct likelihood analysis for missing item scores in multilevel educational data

Abstract: Missing data, such as item responses in multilevel data, are ubiquitous in educational research settings. Researchers in the item response theory (IRT) context have shown that ignoring such missing data can create problems in the estimation of the IRT model parameters. Consequently, several imputation methods for dealing with missing item data have been proposed and shown to be effective when applied with traditional IRT models. Additionally, a nonimputation direct likelihood analysis has been shown to be an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Rather than imputing missing measurements, Mallinckrodt et al [32] suggested the use of a direct likelihood approach to deal with incomplete correlated data under the ignorable assumption. Here, the observed cases are analysed without any analyst's adjustments, that is, without imputation nor deletion, by the use of models that provide a framework where clustered data can be analysed by including both fixed and random effects in the model (in case of GLMMs for non-Gaussian data) [25]. The authors in [25] further showed that DL analysis of incomplete datasets produced unbiased Table 3.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than imputing missing measurements, Mallinckrodt et al [32] suggested the use of a direct likelihood approach to deal with incomplete correlated data under the ignorable assumption. Here, the observed cases are analysed without any analyst's adjustments, that is, without imputation nor deletion, by the use of models that provide a framework where clustered data can be analysed by including both fixed and random effects in the model (in case of GLMMs for non-Gaussian data) [25]. The authors in [25] further showed that DL analysis of incomplete datasets produced unbiased Table 3.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Here, the observed cases are analysed without any analyst's adjustments, that is, without imputation nor deletion, by the use of models that provide a framework where clustered data can be analysed by including both fixed and random effects in the model (in case of GLMMs for non-Gaussian data) [25]. The authors in [25] further showed that DL analysis of incomplete datasets produced unbiased Table 3. Standard errors (Std Err), Bias and mean squared error (MSE) estimates from fully conditional specification (FCS) and multivariate normal imputation methods (MVNI).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In PMI, the mean score of the observed responses of the person is calculated, and the missing values are replaced with values that are generated from random distributions defined by the mean score (Kadengye, Cools, Ceulemans, & Van den Noortgate, 2012). More specifically, the arithmetic mean of an examinee’s observed scores is computed as follows:…”
Section: An Overview Of Missing Data Methodsmentioning
confidence: 99%
“…where PM p is the mean of the observed scores for person p , I rp is the total number of item responses r for person p , and Y pi is the observed response of person p for item i (Kadengye et al, 2012). To add random noise into imputation, PM p is used as a probability to make a random draw from the Bernoulli distribution (Sijtsma & van der Ark, 2003).…”
Section: An Overview Of Missing Data Methodsmentioning
confidence: 99%
“…The rule of imputation is to get the predictive value as close as possible to the missing value, in other words, the imputation tries to minimize the value between the missing value and the predicted value of the missing value. There are two types of data imputation techniques, namely simple imputation [1] and an approximation approach. Simple imputation uses general statistical values, e.g., zero values, mean, median, and random values, while the approximation approach uses prediction values based on other values in the same variable.…”
Section: Introductionmentioning
confidence: 99%